Rechtsmedizin in Japan und in Deutschland – Ein reger wissenschaftlicher Austausch - Püschel, Klaus; Miyaishi, Satoru (Zeitschrift für Japanisches Recht, 2006)
From September 19 to 24, 2005, the “6th International Symposium on Advances in Legal Medicine (ISALM)” was held in Hamburg. It was organized by the German Society of Legal Medicine and the Japanese Society of Legal Medicine in cooperation with the German-Japanese Association of Jurists. The authors took this as an opportunity to give an overview of the development of legal medicine in Japan and Germany, and of scientific exchange today. Regarding the history of legal medicine in Germany, the authors focus on the German Society of Legal Medicine, which celebrated its 100-year anniversary in 2004. In regard to Japan, the authors highlight the foundation of the Japanese Society of Legal Medicine in 1913/14 as a milestone in the history of legal medicine. In Japan, as in Germany, research in the field of legal medicine is mainly the domain of universities. In Japanese legal medicine practice, autopsies are less frequent and clinical legal medicine plays only a minor role, while laboratory tests, experiments, and techniques are of great relevance. The authors then point out the long-established tradition of cooperation and scientific exchange between Japanese and German researchers in the field of legal medicine, which dates back to the 19th century. Finally, the authors give a short history of ISALM. The first symposium was held in 1990 in Kanazawa. Since then symposia have been held every three years to discuss important aspects of legal medicine from a global perspective. ISALM thus continues a well-established tradition of international scientific exchange in the field of legal medicine.